2008
DOI: 10.1007/s11240-008-9338-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of isolated microspore culture of barley (Hordeum vulgare L.): the effect of floret co-culture

Abstract: Barley microspores from five field-grown breeding lines were isolated using an ultra-speed blender and the effect of co-culture with young florets was investigated. Floret co-culture in the induction stage increased the formation of MCS, ELS and green plant regeneration. The florets of teraploid plant were more effective than ones of diploid plant. For line S23, coculture with florets from tetraploid plants gave rise to 2.6 and 7.8 times more MCS and ELS, respectively, than non-co-culture control, whereas co-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 17 publications
1
24
1
Order By: Relevance
“…This may well be the first observation that the gum arabic accelerates the first androgenic cell division in barley. A similar effect was observed when barley microspores were co-cultured with ovaries (Lu et al 2008). In that study, the authors also reported an increase in the frequency of the MCSs formation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This may well be the first observation that the gum arabic accelerates the first androgenic cell division in barley. A similar effect was observed when barley microspores were co-cultured with ovaries (Lu et al 2008). In that study, the authors also reported an increase in the frequency of the MCSs formation.…”
Section: Discussionsupporting
confidence: 76%
“…One way to achieve this is by making use of a nurse culture which secretes various components to the medium to stimulate microspores to rapid divisions and embryo formation. This approach is often used in wheat (Zheng et al 2002;Cistué et al 2006;Broughton 2008) as well as in barley (Li and Devaux 2001;Lu et al 2008;Lippmann et al 2015). However, nurse culture, such as an ovary-culture, can only be used in liquid media and requires additional labor.…”
Section: Introductionmentioning
confidence: 99%
“…Of the different methods for DH production in barley, microspore embryogenesis by anther and/or microspore culture has the greatest potential to produce green DH plants. Even though these methods have been greatly improved in barley (Kasha et al 2001, Cistué et al 1994, Castillo et al 2000, Lazaridou et al 2005, Echavarri et al 2008, Lu et al 2008, Jacquard et al 2006, for review see Ferrie and Caswell 2011, the induction of microspore embryogenesis in cultivars which produce a low number of green plants or none at all, especially in spring genotypes (Muñoz-Amatriaín et al 2008, Asakaviciute 2008, is still a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The microspores were isolated from the pretreated young spikes of barley Hua-30 and cultured in vitro following the procedures described by Lu et al (2008) to induce MDEC (microspore derived embryo callus). After 19-day culture, the induction medium was changed with addition of 8.56 mM·L -1 NaCl as salt stress followed by Liu et al (2016), and the MDECs were collected at 0, 1, 2, 4, 6, 12 and 24 hours after the abiotic treatment for RNA isolation.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%